Code Tracking Algorithms for Mitigating Multipath Effects in Fading Channels for Satellite-Based Positioning. (17th December 2007) - Bhuiyan Bhuiyan, Mohammad Zahidul H. Mohammad Zahidul H.; Lohan Lohan, Elena Simona Elena Simona; Renfors Renfors, Markku Markku
Abstract : The ever-increasing public interest in location and positioning services has originated a demand for higher performance global navigation satellite systems (GNSSs). In order to achieve this incremental performance, the estimation of line-of-sight (LOS) delay with high accuracy is a prerequisite for all GNSSs. The delay lock loops (DLLs) and their enhanced variants (i.e., feedback code tracking loops) are the structures of choice for the commercial GNSS receivers, but their performance in severe multipath scenarios is still rather limited. In addition, the new satellite positioning system proposals specify the use of a new modulation, the binary offset carrier (BOC) modulation, which triggers a new challenge in the code tracking stage. Therefore, in order to meet this emerging challenge and to improve the accuracy of the delay estimation in severe multipath scenarios, this paper analyzes feedback as well as feedforward code tracking algorithms and proposes the peak tracking (PT) methods, which are combinations of both feedback and feedforward structures and utilize the inherent advantages of both structures. We propose and analyze here two variants of PT algorithm: PT with second-order differentiation (Diff2), and PT with Teager Kaiser (TK) operator, which will be denoted herein as PT(Diff2) and PT(TK), respectively. In addition to the proposal of the PT methods, the authors propose also an improved early-late-slope (IELS) multipath elimination technique which is shown to provide very good mean-time-to-lose-lock (MTLL) performance. An implementation of a noncoherent multipath estimating delay locked loop (MEDLL) structure is also presented. We also incorporate here an extensive review of the existing feedback and feedforward delay estimation algorithms for direct sequence code division multiple access (DS-CDMA) signals in satellite fading channels, by taking into account the impact of binary phase shift keying (BPSK) as well as the newly proposed BOC modulation, more specifically, sine-BOC(1, 1) (SinBOC(1, 1)), selected for Galileo open service (OS) signal. The state-of-art algorithms are compared, via simulations, with the proposed algorithms. The main focus in the performance comparison of the algorithms is on the closely spaced multipath scenario, since this situation is the most challenging for estimating LOS component with high accuracy in positioning applications.